Design and use of an ex vivo peripheral simulating bioreactor system for pharmacokinetic analysis of a drug coated stent - Danyi Chen; Colin Krinsky; Mollie Phillips; Catherine Allred; Ava Khan; Linda B. Liu; Uwe Christians; Saami K. Yazdani (Wiley, 2024)
Abstract Currently, there are no ex vivo systems that can model the motion of peripheral arteries and allow for the evaluation of pharmacokinetics (PK) of endovascular devices. The objective of this study was to develop a novel peripheral simulating bioreactor system to evaluate drug pharmacokinetics of stents. We utilized 3D‐printed and off‐the‐shelf components to construct a peripheral‐simulating bioreactor system capable of mimicking the motion of peripheral arteries. Servo motors were primarily used to shorten/elongate, twist, and bend explanted porcine carotid arteries. To evaluate the pharmacokinetics in the bioreactor, drug‐eluting stents were deployed within explanted arteries and subjected to vascular motion along with pulsatile flow conditions. Following 30 min and 24 h, the arteries were removed, and paclitaxel levels were measured. Scanning electron microscopy was also performed to evaluate the stent surface. Arterial paclitaxel levels of the stent‐treated arteries were found to be higher at 30 min than at 24 h following pulsatile and no vascular motion and even higher at 24 h following pulsatile flow and vascular motion. The residual drug on the stent significantly decreased from 30 min to 24 h. Scanning electron microscopy confirmed the loss of paclitaxel coating at 24 h and greater disturbance in stents under peripheral motion versus pulsatile only. This system represents the first ex vivo system to determine the PK of drug‐eluting stents under physiological flow and vascular motion conditions. This work provides a novel system for a quick and inexpensive preclinical tool to study acute drug tissue concentration kinetics of drug‐releasing interventional vascular devices designed for peripheral applications.